PENGARUH PENGGUNAAN TEPUNG TAPIOKA DALAM PEMBUATAN LEM TEGEL KARET - Nesi Susilawati; Rahmaniar Rahmaniar (Balai Riset dan Standardisasi Industri Palembang, 2018)
The purpose of this research is to know effect the addition of tapioca flour to adhesiveness and viscosity of the tile compound rubber glue formulations using filler material. The tile compound rubber glue made from mixture of tapioca flour as filler material. Design research with variation of tapioca flour such as formula A (8 g of tapioca flour), formula B (12 g of tapioca flour), formula C (16 g of tapioca flour), formula D (20 g of tapioca flour) and formula E (24 g tapioca flour) and F (requirements generally and comparison glue). The result showed that the addition of tapioca flour have significant effects on the adhesiveness and viscosity of glue. The higher the addition of tapioca flour (24 g), the adhesiveness would be lower (1.78 kg / in) because of decreased adhesion force. Tiles rubber compound glue formula complied with requirements generally glue (the adhesiveness value of 4.395 kg / in and the Brookfield viscosity value of 98.275 cP is the B formula (tapioca flour 12 g) with an adhesiveness value of 4.17 kg / in and viscosity value 51.33 cP.